Outcome of Bacterial Sepsis in Neonate with Determination of Pathogens and Their Antimicrobial Susceptibility (Bangladesh Critical Care Journal, 2021)
Background: Sepsis in neonate remains a significant cause of mortality and morbidity in developing countries. Neonatal sepsis requires accurate and timely clinical and laboratory diagnosis and proper management for better outcome. In this study an attempt has been made to know the positivity rate of neonatal sepsis, identify the bacterial isolates responsible for EOS and LOS and determine their sensitivity pattern to various antimicrobial agents, and outcome of neonatal sepsis.Methods: A cross sectional descriptive single-centre study was conducted on neonates , over a period of 12 months. Essential investigations were sent by collecting samples under aseptic precautions. Empirical antimicrobial therapy was started according to antimicrobial guidelines in this NICU.Results: Out of 1423 screened blood cultures 13.49% reported as positive and EOS and LOS accounted for 33.85% and 66.15% of cases respectively. Over half (52.60%) of neonates had sepsis with gram negative bacteria and 47.40% with gram positive bacteria and ratio was 1.1:1. Common organisms were Coagulase-Negative Staphylococci-CONS (42.19%), Acinetobacter (22.40%),Enterobacter (18.75%).Total mortality rate was 6.96% & death rate was 23.96% in culture proven sepsis & 04.31% in culture negative isolates (p-value: